EIB Working Paper 2022/13 - COVID-19 and the resilience of European firms The influence of pre-crisis productivity, digitalisation and growth performance - European Investment Bank (European Investment Bank, 2022)
Past research suggests that economic crisis lead to a reallocation of resources from less productive to more productive firms, with many firms taking action to boost their own productivity. This paper uses data from the EIB Investment Survey and the ORBIS database to analyse how the COVID-19 crisis affected the level of employment and digitalisation efforts of European firms. Moreover, it examines how these changes relate to the pre-crisis performance of firms, in terms of productivity, digitalisation and growth. It finds that firms were less likely to reduce their number of employees, both in the short and in the long term, if they exhibited higher productivity or higher growth, or were in highly digitalised sectors. It also finds that firms were more likely to increase their use of digital technologies during the crisis if they were already relatively advanced users of digital technologies.